The Role Of Leadership Style And Work Culture Through Motivation As An Intervening Variable On Employee Performance At PT. Antar Surya Media - Nur Apriliah, Linda; Sundjoto, Sundjoto; Sri Rahayu (Jurnal Ekonomi, 2024)
This study aims to analyze the influence of leadership style and work culture on employee performance, with motivation as a mediating variable at PT. Antar Surya Media. The research method used is Structural Equation Modeling (SEM) to test the relationships between these variables. Data were obtained from 65 employee respondents of PT. Antar Surya Media, and the analysis results show that leadership style and work culture have a significant impact on employee performance. The findings also reveal that leadership style and work culture can directly enhance employee performance without motivation as a mediating factor. Effective leadership and a positive work culture prove to be essential factors in driving optimal performance within the company. The implications of this study highlight the importance of developing supportive leadership and a conducive work culture to boost productivity. This research is expected to provide additional insights for better human resource management development within organizations.